2019
DOI: 10.1101/661116
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Choosing what we like vs liking what we choose: How choice-induced preference change might actually be instrumental to decision-making

Abstract: For more than 60 years, it has been known that people report higher (lower) subjective values for items after having selected (rejected) them during a choice task. This phenomenon is coined "choice-induced preference change" or CIPC, and its established interpretation is that of "cognitive dissonance" theory. In brief, if people feel uneasy about their choice, they later convince themselves, albeit not always consciously, that the chosen (rejected) item was actually better (worse) than they had originally esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
68
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(83 citation statements)
references
References 46 publications
15
68
0
Order By: Relevance
“…The way in which people process information during decision making may be subject to metacognitive control (e.g., Chaxel, 2015), which may lead to rational inattention to different attributes in different choice contexts (Sims, 2003;Caplin & Dean, 2015). The magnitude of shifts in overall evaluations of options tends to increase with the difficulty of the decision (Svenson, 1992), thereby increasing confidence in the choice (Simon, Snow & Read, 2004;Simon & Spiller, 2016;Lee & Daunizeau, 2020a). However, previous studies relating choice difficulty to the magnitude of coherence shifts have not assessed potential changes in the perceived values of those individual attributes that are hypothesized to determine overall value.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The way in which people process information during decision making may be subject to metacognitive control (e.g., Chaxel, 2015), which may lead to rational inattention to different attributes in different choice contexts (Sims, 2003;Caplin & Dean, 2015). The magnitude of shifts in overall evaluations of options tends to increase with the difficulty of the decision (Svenson, 1992), thereby increasing confidence in the choice (Simon, Snow & Read, 2004;Simon & Spiller, 2016;Lee & Daunizeau, 2020a). However, previous studies relating choice difficulty to the magnitude of coherence shifts have not assessed potential changes in the perceived values of those individual attributes that are hypothesized to determine overall value.…”
Section: Introductionmentioning
confidence: 99%
“…An increased coherence shift for high disparity choices would in turn increase choice confidence and decrease response time (RT), as the choice effectively becomes easier (cf. Lee & Daunizeau, 2020a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of studies of cognitive dissonance theory in CIPC, it has been debated when the preference change occurs, during the choice phase or during the post-choice subjective rating phase. Lee and Daunizeau [10] indicated that the process of restoring cognitive consistency occurs during the decision process rather than during the post-ratings. In addition, Nakao et al [12] reported a link between CIPC and brain activity around 400 ms after choice.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, choice-based learning (CBL) has been proposed to describe the CIPC phenomenon [9][10][11][12][13], in which the values of both the chosen and rejected items are updated as if the own choice is regarded as a correct answer. The CBL model was first proposed by Akaishi et al [9] and revealed the tendency of people to make the same decision on perceptually ambiguous stimuli without feedback.…”
Section: Internally Guided Decision-making (Idm) and Computational Momentioning
confidence: 99%